Effects of vitamin A supplementation on visual function in healthy adults: A systematic review - Kavous Shahsavarinia; Ali Mostafaei; Nooshin Milanchian; Leila Roshangar; Parastu Fallahi; Moloud Balafar; Robab Mehdipour; Fereshteh Farhadi; Hassan Soleimanpour; Nasim Hajipoor; Reza Mohammadi; Hanieh Salehi-Pourmehr (مجله پزشکی دانشگاه علوم پزشکی تبریز)
Background. Vitamin A plays an important role in various bodily functions, including vision. This systematic review aimed to synthesize the available evidence on the effects of vitamin A supplementation on visual function in healthy adults. Methods. A comprehensive search of electronic databases was conducted to identify randomized controlled trials investigating the effects of vitamin A supplementation on visual function in healthy adults. The methodological quality of the included studies was assessed using the Cochrane Collaboration tool. Data extraction and analysis were performed to determine the overall effect of vitamin A supplementation on visual outcomes. Two reviewers independently assessed the studies for biases, with disagreements resolved by a third reviewer. The quality of the articles was evaluated in accordance with existing standards, with any disagreements resolved through discussion or referral. Results. A search of 12945 articles from databases led to 276 full-text articles being evaluated, resulting in 17 studies. These studies examined the effects of lutein and zeaxanthin supplementation on macular pigment optical density (MPOD) and visual function. Results showed a positive correlation between MPOD and temporal contrast sensitivity function, with both improving after supplementation. However, a study by Bartlett did not find significant improvements in visual function. Most studies showed positive effects on MPOD and visual function, but the clinical significance and optimal dosage and duration remain unclear. Most studies had medium to high quality evidence. Conclusion. Vitamin A, Lutein, and zeaxanthin supplementation may improve visual function, but optimal dosage, duration, and carotenoid combination are not yet established. Long-term safety and efficacy require further investigation, including standardized assessments, longer follow-ups, diverse populations, and mechanistic studies. Practical Implications. While current research indicates that supplementing with lutein and zeaxanthin may offer benefits like improved contrast sensitivity and macular pigment density, the inconsistent findings highlight that we don't yet have a clear understanding of who will benefit most, the ideal dosage, or how long supplementation is effective for healthy adults. Therefore, widespread recommendations for these supplements to enhance vision in the general healthy population cannot be made at this time, and individuals should consult with healthcare professionals before starting any supplementation.